Al-Arḋ fī Al-Qur’ān al-Karīm; Taḥlīl Dalālī li al-Mafhūm - Rasheed, Ebaa Younis; Ahmed, Jotyar Idris (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This research aims to investigate the word "earth" in the Holy Qur'an and found that it came in (461) places; despite its frequent occurrence in the Holy Qur'an, the points of analysis of this study were limited، and the cause is not absent from the distinguished minds. Most of the verses in which the concept of "earth" was mentioned indicated divine power and cosmic beauty. For the above reason، the research was chosen to analyze (48) locations only with the pronouns that the concept of land carries when the Qur'an continues to present the story of the concept through the verses of the Holy Qur'an and the concept has been treated within the theory of semantic analysis. This research is qualitative and uses a type of literature study. The research data is based on the concept of "earth" and is sourced from the Qur'an. The data collection technique is carried out by documentation. Meanwhile, the data analysis is descriptive-interpretive. Among the findings of the research by adding the term "ahl" to the concept it was found that the people despite their ethnic and relative differences but when they are linked to the concept they are considered one people as they are for one ruler the Almighty said: Pharaoh exalted himself in the land and made its people parties [Al-Qasas: 4] And by adding the term "khazāin" to the concept of a special positive connotation that would not have been available without the presence of the concept the Qur'anic structure did not show the state treasures for example or the treasures of Egypt as it came in the story of Joseph - peace be upon him - he said"Let me be in charge of the land's treasures I am the All-Knowing Guardian" (Yusuf: 55).